MURDER ON THE RAILWAYS - Haining, Peter (London, : Bounty Books, 1996)
Express to Stamboul / Agatha Christie -- Crime on the footplate / Freeman Wills Crofts -- The man with no face / Dorothy L. Sayers -- Dead man / James M. Cain -- Cheese / Ethel Lina White -- A curious suicide / Patricia Highsmith -- Jeumont: 51 minutes' wait / Georges Simenon -- Three-ten to Yuma / Elmore Leonard -- The adventure of the first-class carriage / Ronald A. Knox -- The murder on the Okehampton Line / Victor L. Whitechurch -- The mystery of the black blight / Francis Lynde -- The knight's cross signal problem / Ernest Bramah -- Once upon a train / Craig Rice and Stuart Palmer -- The Rhine maiden / Leslie Charteris -- Murder on the 7.16 / Michael Innes -- Murder in the tunnel / Brian Hunt -- A mystery of the underground / John Oxenham -- Death in the air / Cornell Wollrich -- The mysterious death on the underground railway / Baroness Emmuska Orczy -- Thubway Tham's bomb scare / Johnston McCulley -- The Coulman handicap / Michael Gilbert -- A midnight train to nowhere / Ken Follett -- Oxford circus / Maeve Binchy -- Drink entire: against the madness of crowds / Ray Bradbury -- The riddle of the 5.28 / Thomas W. Hanshew -- Headhunter / Jan Carol Sabin -- Escape to danger / Erle Stanley Gardner -- Death decision / William F. Nolan -- Broker's special / Stanley Ellin -- Galloping Foxley / Roald Dahl -- The second passenger / Basil Copper -- The green road to Quephanda / Ruth Rendell